(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article investigates the development of physical culture competence among university students in the context of distance learning, with a particular focus on the Kherson region, currently situated in an active combat zone. It examines a range of pressing issues, challenges and limitations related to organising physical education in an online format during wartime. The authors present effective methodological approaches and tools that contribute to preserving and developing physical culture competence within student youth in today’s extreme conditions. The traditional physical education process faces significant obstacles in the Kherson region under martial law, which is characterised by an unstable internet connection, frequent power outages, psychological stress and limited opportunities for active physical activity. The study highlights the psychophysical difficulties experienced by students and emphasises the importance of tailoring classes and utilising digital platforms, mobile applications and communication support. The authors stress the need to create an educational and motivational environment in which physical activity becomes an integral part of students’ daily lives. Although the distance learning format cannot fully replace traditional classes, it can effectively complement them within a blended learning framework, encouraging independent and motivated learning among students. The study emphasises that successful development of physical culture competence depends on the pedagogical mastery and digital competence of instructors, student engagement through interactive formats, task individualisation and the availability of technical and psycho-emotional support. Further research may focus on examining the long-term impact of distance physical education on motor activity, physical health and psycho-emotional state of university students.